Does Public Health Insurance Coverage Lead to Better Health Outcomes? Evidence From Chinese Adults. (April 2019) - Fan, Hongli; Yan, Qingyue; Coyte, Peter C.; Yu, Wenguang
This article examines the impacts of public health insurance on the health of adults through use of data from the China Health and Nutrition Survey. We use the endogenous treatment effects model to infer the causal effects of public health insurance on health. We find that public health insurance significantly improves the physical and mental health status of health insurance beneficiaries after controlling for other covariates. Among the 2 types of voluntary public health insurance, the Urban Resident Basic Medical Insurance has the greater impact in improving health than the New Cooperative Medical Scheme. Moreover, the health effect appears to be stronger for middle-aged individuals, the elderly, and those with lower incomes than for their counterparts. The positive health effects may result from few channels, including the increase of health care utilization, the improvement of health-related behaviors, and the fact that individuals with public health insurance are more likely to use higher level care providers. This study provides implications on reforming China's health care system.